(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To conduct a preliminary assessment of the content validity and reliability of the Vietnamese version of the H-PEPSS among clinical nurses. Methods: A methodological study was conducted at Hospital for Traumatology and Orthopaedics at Ho Chi Minh city from January to June 2025. The H-PEPSS was translated using a forward-backward translation process with contextual adaptation. Content validity was assessed by six experts using the item-level content validity index (I-CVI) and the scale-level content validity index (S-CVI/Ave). Reliability was evaluated using Cronbach’s Alpha for internal consistency and intraclass correlation coefficient (ICC) for test-retest reliability after a one-week interval among 30 clinical nurses. Results: All 16 items achieved an I-CVI of 1.0, and the S-CVI/Ave was 1.0. The overall Cronbach’s Alpha was 0.90, with subscale values ranging from 0.72 to 0.90. The overall ICC was 0.93, with subscale ICCs ranging from 0.747 to 0.94. These findings indicate excellent content validity, good internal consistency, and high temporal stability in the preliminary testing phase. Conclusion: The Vietnamese version of the H-PEPSS demonstrated satisfactory psychometric properties for preliminary use in assessing nurses’ patient safety competence. Further studies with larger and more diverse samples are needed to examine its structural validity and broader applicability.